Sejarah Masuknya Islam di Tanah Karo dan Peninggalan Sejarah Islam di Tanah Karo - Tanjung, Flores; Sinaga, Rosmaida; br Tarigan, Talenta; Br Surbakti, Adelia Charoline Amayta; Br Tarigan, Ade Leora; Siagian, Deviyana Sri Marini (Universitas Pahlawan Tuanku Tambusai, 2024)
If you are on vacation in Tanah Karo in North Sumatra, take the time to stop by the Old Mosque of Kabanjahe. Historically, the mosque is the first and oldest in Karo. The city of Kabanjahe in Karo Regency keeps a historical trace of the spread of Islam by traders. This can be seen from a historical building that still stands in this city. The building is the Old Mosque of Kabanjahe. The Old Kabanjahe Mosque is located at Jalan Masjid, Lau Cimba Village, Kabanjahe and is the first and oldest mosque in Tanah Karo. This mosque was built in 1902 and was completed two years later in 1904.